IDENTIFYING RELEVANT SUSTAINABILITY COMPONENTS FOR LOCAL ROAD PAVEMENT - Handayani, Fajar Sri; Pramesti, Florentina Pungky; Setyawan, Ary; Sangadji, Senot (Journal of Applied Engineering Science, 2025)
To ensure our sustainable future, the whole lifecycle of our current and newly built infrastructure must satisfy sustainable standard, focusing Sustainable Development Goals (SDG) 13.  It should meet functional requirements of reducing negative impacts to the environment while at the same time support economic growth and societal development. Due to its vast network, local roads may contribute to sustainable living assuming that it is designed, constructed, operated, and maintained in such a way that satisfy sustainable standard. Despite the fact that sustainable road rating systems have been developed in many countries, there is no agreement on the components for defining and measuring local road sustainability, especially in developing countries. In facilitating the development of the future local road sustainability index, this paper attempts to identify the components by finding insights and agreement from experts. In this case Delphi technique was employed. Seventeen components were specified consists of eleven environmental components, three economic components, and two social components. This means that the achievement of local roads sustainability integrates the three aspects; environmental stewardship, economic growth, and social development.
Keywords: sustainability, relevant component, Delphi method, local road